Investigation of Image Processing Techniques in MRI Based Medical Image Analysis Methods and Validation Metrics for Brain Tumor - Kalaiselvi, T.; Karthigai Selvi, S. (Current Medical Imaging, 2018)
Background: This paper reviews the recent techniques employed to process brain tumor images from Magnetic Resonance (MR) images. Automation in tumor and its sub-compartment segmentation from MR images is rising and necessary in rapid diagnosis and planning of human brain treatment. Discussion: The success of fine tumor segmentation depends on an entire pipeline of the processes such as preprocessing, segmentation, feature extraction and classification tools. Conclusion: Hence, the review aims to present a collective overview of existing techniques and explore the metrics which are used for various performance analysis for image processing techniques.
Keywords: classification